The RNA helicase DDX3 and its role in c-MYC driven germinal center-derived B-cell lymphoma - Lacroix, Marion; Beauchemin, Hugues; Khandanpour, Cyrus; Möröy, Tarik (Frontiers in Oncology, 2023)
DDX3X is an RNA helicase with many functions in RNA metabolism such as mRNA translation, alternative pre-mRNA splicing and mRNA stability, but also plays a role as a regulator of transcription as well as in the Wnt/beta-catenin- and Nf-κB signaling pathways. The gene encoding DDX3X is located on the X-chromosome, but escapes X-inactivation. Hence females have two active copies and males only one. However, the Y chromosome contains the gene for the male DDX3 homologue, called DDX3Y, which has a very high sequence similarity and functional redundancy with DDX3X, but shows a more restricted protein expression pattern than DDX3X. High throughput sequencing of germinal center (GC)-derived B-cell malignancies such as Burkitt Lymphoma (BL) and Diffuse large B-cell lymphoma (DLBCL) samples showed a high frequency of loss-of-function (LOF) mutations in the DDX3X gene revealing several features that distinguish this gene from others. First, DDX3X mutations occur with high frequency particularly in those GC-derived B-cell lymphomas that also show translocations of the c-MYC proto-oncogene, which occurs in almost all BL and a subset of DLBCL. Second, DDX3X LOF mutations occur almost exclusively in males and is very rarely found in females. Third, mutations in the male homologue DDX3Y have never been found in any type of malignancy. Studies with human primary GC B cells from male donors showed that a loss of DDX3X function helps the initial process of B-cell lymphomagenesis by buffering the proteotoxic stress induced by c-MYC activation. However, full lymphomagenesis requires DDX3 activity since an upregulation of DDX3Y expression is invariably found in GC derived B-cell lymphoma with DDX3X LOF mutation. Other studies with male transgenic mice that lack Ddx3x, but constitutively express activated c-Myc transgenes in B cells and are therefore prone to develop B-cell malignancies, also showed upregulation of the DDX3Y protein expression during the process of lymphomagenesis. Since DDX3Y is not expressed in normal human cells, these data suggest that DDX3Y may represent a new cancer cell specific target to develop adjuvant therapies for male patients with BL and DLBCL and LOF mutations in the DDX3X gene.